Effects of oral amino acid supplementation on Multidimensional Prognostic Index in hospitalized older patients: a multicenter randomized, double-blind, placebo-controlled pilot study - Volpato S (Dove Medical Press, 2018)
Stefano Volpato,1 Romina Custureri,2 Matteo Puntoni,3 Lara Bianchi,1 Julia Daragjati,4 Sara Garaboldi,2 Matteo Simonato,4 Antonio Greco,5 Emanuele Rizzo,6 Pierluigi Dal Santo,7 Antonio Mangiacotti,5 Ekaterini Zigoura,2 Giacomo Siri,3 Alberto Pilotto2 1Department of Medical Science, University of Ferrara, Ferrara, Italy; 2Department of Geriatric Care, Orthogeriatrics and Rehabilitation, E.O. Galliera Hospital, Genova, Italy; 3Clinical Trial Unit, Scientific Directorate, E.O. Galliera Hospital, Genoa, Italy; 4Geriatrics Unit, San Antonio Hospital, ULSS 6 Euganea, Padova, Italy; 5Geriatrics Unit, IRCCS Casa Sollievo della Sofferenza, San Giovanni Rotondo, Foggia, Italy; 6Geriatrics Unit, ULSS 2 Marca Trevigiana, Montebelluna, Italy; 7Geriatrics Unit, ULSS 5 Polesana, Rovigo, Italy Background: It is not known whether amino acid supplementations may influence health status in hospitalized older acutely ill patients. Aim: The aim of this study was to determine whether nutritional supplementation with amino acids (Aminoglutam®) is associated with multidimensional improvement assessed with the Multidimensional Prognostic Index (MPI). Methods: In this randomized, double-blind, placebo-controlled pilot clinical trial, 126 patients aged ≥65 years were enrolled from 6 Italian geriatric wards. A multidimensional assessment to calculate the MPI was performed at baseline and after 4 weeks of treatment with nutritional supplementation (96 kcal, 12 g amino acids, 0.18 g fat, 11.6 g carbohydrate, and vitamins B1, B6, and C) or placebo administered twice a day. Logistic regression modeling was applied to determine the effect of treatment on the improvement of MPI (vs no-change/worsening), adjusting for gender, age, and MPI at baseline. Treatment’s interactions with age, gender, and MPI at baseline were tested adding the appropriate interaction parameter in the regression models. Results: Of the 126 patients included, 117 patients (93%) completed the study. A significant improvement in the MPI score was detected in the overall population (mean difference post-pretreatment: -0.03, p=0.001), with no differences between active and placebo arms. Men in the amino acid supplementation group had a significantly higher rate of improvement in MPI (81%) compared to the placebo group (46%) (Fisher’s exact test p=0.03). Adjusting for age, diagnosis, and MPI at baseline, amino acid treatment was shown to be associated with an improvement in MPI in men (OR=4.82, 95% confidence interval [CI]: 0.87–26.7) and not in women (OR=0.70, 95% CI: 0.27–1.81). The interaction effect between active treatment and gender was significant (p=0.04). Conclusion: A 4-week amino acid supplementation improved the MPI significantly in hospitalized older male patients but not in female patients. Further studies are needed to confirm the gender effect of amino acid supplementation on MPI in older patients. Keywords: Multidimensional Prognostic Index, aging, hospitalization, oral supplementation, amino acids